SlCCD1A Enhances the Aroma Quality of Tomato Fruits by Promoting the Synthesis of Carotenoid-Derived Volatiles - Guo-Ting Cheng (MDPI AG, 2021)
The loss of volatiles results in the deterioration of flavor in tomatoes. Volatiles are mainly derived from fatty acid, carotenoid, phenylpropane, and branched chain amino acids. In this study, the tomato accession CI1005 with a strong odor and accession TI4001 with a weak odor were analyzed. The volatile contents were measured in tomato fruits using gas chromatography-mass spectrometry. The scores of tomato taste and odor characteristics were evaluated according to hedonistic taste and olfaction. It was found that the content of fatty acid-derived volatiles accounted for more than half of the total volatiles that had grassy and fatty aromas. Phenylpropane-derived volatiles had irritation and floral aromas. Branched-chain amino acid-derived volatiles had a caramel aroma. Carotenoid-derived volatiles had floral, fruity, fatty, and sweet-like aromas, preferred by consumers. A lack of carotenoid-derived volatiles affected the flavor quality of tomato fruits. The accumulation of carotenoid-derived volatiles is regulated by carotenoid cleavage oxygenases (CCDs). A tissue-specific expression analysis of the SlCCD genes revealed that the expression levels of SlCCD1A and SlCCD1B were higher in tomato fruits than in other tissues. The expression levels of SlCCD1A and SlCCD1B were consistent with the trend of the carotenoid-derived volatile contents. The expression of SlCCD1A was higher than that for SlCCD1B. A bioinformatics analysis revealed that SlCCD1A was more closely linked to carotenoid metabolism than SlCCD1B. The overexpression of SlCCD1A indicated that it could cleave lycopene, α-carotene, and β-carotene to produce 6-methyl-5-hepten-2-one, geranylacetone, α-ionone, and β-ionone, increasing the floral, fruity, fatty, and sweet-like aromas of tomato fruits. The flavor quality of tomato fruits could be improved by overexpressing SlCCD1A.